Preliminary procedures for detecting crime - Hocine, Nesma (Journal of Human Sciences, 2023)
The offender always seeks to obliterate the features of his crime and not to leave any trace through which it can be inferred and the most important thing facing the criminal investigator in this case is to work to prove the facts and save what has been seen and collected at the place of committing the crime in all details and the union of all legal procedures about it as of paramount importance un detecting the crime and holding the offender accountable, using the scientific method and modern techniques with reliance on the efficiency of these investigators in dealing with the criminal consequences that are later formed evidence of the involvement of the offender in the commission of the crime .